Geochronology of Early Cretaceous copper mineralization at the NE China-North Korea border - Zhang, Yong; Song, Quan-Heng; Xing, Shu-Wen (International geology review, 2019)
North Korea is host to world-class metallic mineral deposits, such as the Komdok Cu-Pb-Zn polymetallic mineral belt, but little is known about the resource. To better understand the genesis of the Cu mineralization around the China-North Korea border, we determined the U-Pb, Re-Os, and Rb-Sr ages of three deposits in the area. Sulfide samples from the Hyesan Cu deposit produced Rb-Sr isochron ages of 127.4 ± 4.5 Ma. The Wanbaoyuan Cu deposit yielded a molybdenite Re-Os isochron age of 127.5 ± 3.2 Ma, and a granodiorite sample from the Linjiang Cu deposit gave a zircon U-Pb age of 129.5 ± 0.8 Ma. Combined with geochronological data from previous studies, these new ages suggest that the Cu mineralization occurred mainly during the Cretaceous, and the rollback of the Paleo-Pacific Plate was responsible for the Cu mineralization in NE China-North Korea border.